Educational inequality in Mexico: Differences in learning reading comprehension in basic education - Backhoff, Eduardo (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
Globally, the socioeconomic status of families is the variable that is most closely linked to student learning. However, the impact exerted by socioeconomic status varies from country to country. The size of these differences is an indicator of the degree of inequality of educational systems and a way to estimate to what extent the most vulnerable groups in a country are affected. One way to measure the strength of this variable is through a measure known as the socioeconomic gradient. Based on this indicator, in 2007 the National Institute for Educational Evaluation (INEE) conducted a Mexican survey on basic education to estimate the size of the gradients of the School Cultural Capital in Mexico and in its 32 states. Since the study was only published in a technical report, this work is twofold: to present the methodology for estimating the socioeconomic gradient and report on the degree of inequality in basic education in Mexico. Results are presented for sixth graders on reading comprehension. It concludes with a summary and interpretation of results.